Empowering Teachers Through Training in Designing Pancasila Student Profile (P5) Strengthening Projects for Chemistry Teachers Using the STEM Approach - Kurniawan, Cepi; Budi Susatyo, Eko; Nurhayati, Sri (Jurnal Abdimas, 2024)
This paper aims to empower chemistry teachers by providing training on designing projects that strengthen the Pancasila Student Profile (P5) through the Science, Technology, Engineering, and Mathematics (STEM) approach. The Pancasila Student Profile is an educational initiative in Indonesia that emphasizes the development of students' character, competencies, and values in line with Pancasila, the nation's philosophical foundation. The integration of STEM into this initiative seeks to equip teachers with the skills and knowledge necessary to foster a holistic learning environment. The training was conducted over several sessions, involving a combination of theoretical presentations and practical workshops. Data were collected through pre- and post-training assessments, observations, and interviews with participants. The results indicate a significant improvement in the participants' ability to design and implement P5 projects with a STEM focus, suggesting that such training can be an effective tool for enhancing educational quality in Indonesia.